Digital economy and carbon emission performance: Evidence at China's city level - Zhang, Wei; Liu, Xuemeng; Wang, Die; Zhou, Jianping (Energy policy, 2022)
This paper discusses the effect and mechanisms of digital economy (diec) on carbon emission performance (cop). Specifically, based on the panel data of 277 cities in China from 2011 to 2019, carbon emission performance and digital economy at the city level were evaluated through global super efficiency Epsilon-Based Measure (EBM) with unexpected output, and the vertical and horizontal scatter degree method, respectively. The OLS, mediation effect model, threshold model and spatial Durbin model (SDM) were adopted to investigate the nexus of diec and cop. The results show that: First, digital economy improves carbon emission performance, and this conclusion holds even after a series of robustness tests and endogenous treatment. The main impact mechanisms are energy intensity (ei), energy consumption scale (ec) and urban afforestation. And the effect and its impact mechanisms show regional heterogeneity. Second, under different levels of energy consumption structure, ei, ec, government intervention and urban afforestation, the impact of diec on cop is non-linear. Third, there's a spatial effect between diec and cop. The impact of diec on cop is significantly positive in local cities, while insignificant in the neighboring cities. Based on the above conclusions, specific recommendations are proposed for diec to improve cop. •The development level of digital economy of 277 cities in China was estimated.•Global super-efficiency EBM model was employed to measure carbon emission performance.•The nexus of digital economy and carbon emission performance (cop) was investigated.•Digital economy improves cop, but with non-linear and spatial effects.•Enhance the integration of digital economy with carbon emission reduction.